Identification of Genes and Pathways Associated with Kidney Ischemia-Reperfusion Injury by Bioinformatics Analyses - Wei Feng; Rongwei Tang; Xudong Ye; Chao Xue; Yunhua Liao (Karger Publishers, 2016)
Background/Aims: Ischemia-reperfusion (IR) injury in the kidney is a major cause of acute kidney injury in humans. However, the molecular mechanisms responsible for the progression of kidney IR injury still need to be explored. In this study, we aimed to explore the underlying genes and pathways associated with kidney IR injury. Methods: Gene microarray of GSE27274 was downloaded from the Gene Expression Omnibus database. The differentially expressed genes (DEGs) between kidney IR injury and kidney IR rat samples were analyzed. Gene Ontology biological process (BP) and pathway enrichment analyses of DEGs were performed, followed by protein-protein interaction (PPI) network construction. Results: A total of 88 up-regulated and 102 down-regulated DEGs were identified. The up-regulated DEGs including FK506 binding protein 1A (Fkb1a) were mainly enriched in biological processes (BPs) related to protein ubiquitination. The down-regulated DEGs including complement component 5 (C5) were enriched in complement and coagulation cascades pathway. Choline phosphotransferase 1 (Chpt1) was enriched in glycerophospholipid metabolism pathway. In the PPI network, heme oxygenase (decycling) 1 (Hmox1) was as a hub gene that interacted with the maximum nodes. Conclusions: DEGs of Fkb1a, C5, Chpt1, and Hmox1, as well as complement and coagulation cascades pathway, glycerophospholipid metabolism pathway, and BP terms related to protein ubiquitinatione may be the potential targets for diagnosis and treatment of kidney IR injury.